Data collection from experimental PV system - Kulkarni, Pratham Prasanna (České vysoké učení technické v Praze, 2025)
This work explores the field of data collection and analysis for photovoltaic systems, with a focus on the implementation aspects of the data acquisition system. The work combines research and applies the findings to the practical implementation. Initially, research on the basic principles of photovoltaic systems was conducted to establish a foundational understanding of their operation. Furthermore, to expand knowledge of the work's scope, research was conducted on data acquisition systems and their integration in photovoltaic systems. This allowed for a concrete understanding of the implementation. Prior to the implementation, the photovoltaic system was mapped, and all components and their current conditions were described. The data acquisition system was implemented by integrating Unipi into the photovoltaic system. Energocentrum Plus, s.r.o. completed this integration. As part of the scope of this work, a program was created in Python that collected data from Unipi and stored it in real-time. Using the Dash and Plotly libraries in Python, a dashboard was created that displays live data and historical data based on the stored values.

This work explores the field of data collection and analysis for photovoltaic systems, with a focus on the implementation aspects of the data acquisition system. The work combines research and applies the findings to the practical implementation. Initially, research on the basic principles of photovoltaic systems was conducted to establish a foundational understanding of their operation. Furthermore, to expand knowledge of the work's scope, research was conducted on data acquisition systems and their integration in photovoltaic systems. This allowed for a concrete understanding of the implementation. Prior to the implementation, the photovoltaic system was mapped, and all components and their current conditions were described. The data acquisition system was implemented by integrating Unipi into the photovoltaic system. Energocentrum Plus, s.r.o. completed this integration. As part of the scope of this work, a program was created in Python that collected data from Unipi and stored it in real-time. Using the Dash and Plotly libraries in Python, a dashboard was created that displays live data and historical data based on the stored values.
Data collection from experimental PV system
Keywords: Solar Energy; Photovoltaic System; Data Acquisition System; Photovoltaic Monitoring; Python Dashboard; Real-time Data Visualization; Supervisory Control and Data Acquisition; Unipi Neuron; Photovoltaic Inverters; Renewable Energy Data Logging; Photovoltaic Data Processing; Solar Energy; Photovoltaic System; Data Acquisition System; Photovoltaic Monitoring; Python Dashboard; Real-time Data Visualization; Supervisory Control and Data Acquisition; Unipi Neuron; Photovoltaic Inverters; Renewable Energy Data Logging; Photovoltaic Data Processing